2007
DOI: 10.1182/blood-2007-01-068411
|View full text |Cite
|
Sign up to set email alerts
|

p52Shc is required for CXCR4-dependent signaling and chemotaxis in T cells

Abstract: ShcA is an important mediator of Ras/ MAPK activation in PTK-regulated pathways triggered by surface receptors. This function is subserved by the constitutively expressed p52-kDa isoform. Besides activating Ras, p52Shc couples the TCR to Rho GTPases, and thereby participates in actin cytoskeleton remodeling in T cells. Here we have addressed the potential involvement of p52Shc in T-cell chemotaxis and the role of the phosphorylatable tyrosine residues, YY239/240 and Y317, in this process. We show that CXCR4 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…In this regard, it has recently been shown that the cytosolic adapter protein Shc is phosphorylated upon CXCR4 stimulation and assembles into a complex that includes Lck, ZAP70, Vav1, and LAT (59). Moreover, Shc-deficient Jurkat T cells show an attenuated migratory capacity and impaired F-actin dynamics upon CXCR4 stimulation, and mutation of critical tyrosine residues of Shc (YY 238/240 or Y 317 ) results in defective phosphorylation of Vav1 and Itk (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it has recently been shown that the cytosolic adapter protein Shc is phosphorylated upon CXCR4 stimulation and assembles into a complex that includes Lck, ZAP70, Vav1, and LAT (59). Moreover, Shc-deficient Jurkat T cells show an attenuated migratory capacity and impaired F-actin dynamics upon CXCR4 stimulation, and mutation of critical tyrosine residues of Shc (YY 238/240 or Y 317 ) results in defective phosphorylation of Vav1 and Itk (59).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Shc-deficient Jurkat T cells show an attenuated migratory capacity and impaired F-actin dynamics upon CXCR4 stimulation, and mutation of critical tyrosine residues of Shc (YY 238/240 or Y 317 ) results in defective phosphorylation of Vav1 and Itk (59). Thus, Shc might be an attractive candidate to connect CXCR4 with the Vav1-Itk-dependent pathway of F-actin polymerization and T cell migration (59). It will be important to assess the role of Shc in CXCR4-induced inside-out signaling, adhesion, and Rap1 activation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2+ concentrations were determined in cells loaded with 3 mM Fura-2 (Molecular Probes) in 140 mM NaCl, 5.4 mM KCl, 1 mM MgCl 2 , 0.2 mM EGTA, and 15 mM HEPES (pH 7.4) in the presence of 1 mM Ca 2+ , as described (26). Loaded cells were sensitized with anti-DNP IgE (1 mg/ml) on ice for 1 h and stimulated with DNP-ALB (1 mg/ml or 20 ng/ml), thapsigargin (2 mM), or ATP (3 mM).…”
Section: Flow Cytometry and Ca 2+ Flux Analysismentioning
confidence: 99%
“…Following the in vitro treatment, 1 Â 10 6 live cells/sample (as determined by trypan blue exclusion) were loaded in Transwell filters (Costar, Corning, 5 mm pores) which were placed in 24-well plates containing medium without additives or with 100 ng/mL SDF-1a as described [45] as well as drugs. Loading control samples were set up by plating 1 Â 10 6 live cells, treated as above, in 24-well plates containing RPMI supplemented with 0.5% serum and drugs.…”
Section: Transwell Migration Assaysmentioning
confidence: 99%